Ecological Characteristic of Grazing Vegetation and Capacity Food for the Large Cattle in Central Highland, Vietnam - Tai, Vu Anh; Thi Thuy Van, Tran; Quang Tuan, Bui; Duc Hoang, Le (VNU Journal of Science: Earth and Environmental Sciences, 2021)
The Highland Central of Vietnam has a high potential for livestock development with a vast grazing areas include scrubs, grassland and some forest types. Currently, the livestock of the Central Highland has been facing with water shortage when dry season has prolonged from 4 to 6 months that make most of the plant communities stop growing. In order to develop livestock in the Central Highland, the ecological characteristics of the natural vegetation were gathered, including structure, seasonal rhythm and succession trend of each plant communities related to grazing. In this paper, the ecological characteristics of 11 natural ecological habitats and one artificial habitat were described. In addition, natural grazing vegetation includes five forests, three scrubs and three grasslands belonging to three bio-climate types (tropical monsoon moisture, tropical monsoon dry and sub-tropical monsoon moisture) and three ecological canopy types (evergreen, semi-deciduous and deciduous) were analyzed. The seasonal rhythm of each ecosystem affected the food resources for the cattle. In which, the main food was found in dry grasslands and scrubs in the rainy season while those habitats have not supported food considerable in the dry season. Thus, the cattle would get food from the moisture habitats in this period. The largest changes of food source ratios between rainy and dry seasons were found in Dak Lak and Gia Lai provinces, where the dry habitats are common. On contrary, the changing ratios at Kon Tum and Lam Dong provinces have been not much. Hence, these two provinces would support stably food for the large cattle during the year. However, when the density of the cattle head is too high, the natural food sources cannot adapt for the cattle requirement especially in the dry season. Thus, people must use the other sources such as planting, industrial food for cattle feeding. The density of the cattle also affected the ecological succession trend of each habitat. In normally, the forest would be changed to the scrubs and the scrubs would be changed to the grassland, and vice versa. In the first trend, it is positive but the second trend is negative. Because of high density of cattle, the negative ecological succession within the natural vegetation related to the grazing in the Central Highland has been found at the western area of Dak Lak and Gia Lai provinces, and most areas of Kon Tum and Dak Nong provinces except the habitat along the boundary of the special used forest (national park, nature reserves). The positive succession would be found at all of the special used forest areas, Lam Dong province, Southeastern area of Dak Lak province, Central areas of Gia Lai province